Knowledge, attitude, belief and perception on breast cancer and screening practices among Ghanaian immigrants living in Germany and compatriots living in Ghana - Mandy Opoku-Amankwah (2022)
Background: Breast cancer is the most common cancer in both developing and developed countries and is the leading cause of cancer mortality in women. Breast cancer in women is considered a huge public health problem in Ghana with critical effect on the healthcare systems and medical expenditure. Objectives: The aim of this study is to investigate on the knowledge, attitudes, belief and perception on breast cancer and screening practices among Ghanaian immigrants living in Germany and compatriots living in Ghana. Methods: A cross-sectional study was performed on 200 Ghanaian women between 20 to 60 years old living in Hamburg, Germany and Kumasi, Ghana. 100 participants from each countries of residence. The demographic characteristics, reproductive history, knowledge, belief, breast cancer, screening practices and the geographical differences on breast cancer screening. Participants were assessed through an online survey questionnaire. Results: The mean age of the participants in the study for women living in Hamburg, Germany (30.44±6.7) and Kumasi, Ghana (30.58±9.1). Most of the participants in the study revealed a high level of education up to Tertiary level in both countries of residence (HG 79%, KG 91%). The study revealed a statistically significant association between the educational status and self-reported knowledge on both breast cancer and screening practices. Mann-U Whitney HG (U=4327, P=.008) KG (5000, P=.008). There was no statistical association between the religious status and knowledge on breast cancer and screening practices (HG (U=4999, P=.997) KG (5000, P=1.000). There was a statistically significant association between the age and self-reported knowledge on breast cancer and screening practices HG (U=9602, P=.018) KG (9130, P=.028).A large proportion of the participants usually get their source of information from the media and medical practitioners in both countries of residence. Media (HG55%, KG 56%) Medical practitioners (HG32%, KG30%). Conclusion: The study revealed that the level of knowledge, awareness and perception about breast cancer and screening practices among Ghanaian women in both countries of residence is very high, and the participants proved good level of screening practices. More research should be conducted on the prevalence of the breast cancer in Ghana.